The Republic of Lithuania before Presidency of the Council of the European Union in the Second Half of 2013 (Economic and Political Thought, 2013)
From 1 July 2013 the Republic of Lithuania will start its first presidencyof the Council of the European Union. Since the Treaty of Lisbon cameinto force, Lithuania will participate in the third trio-presidency. It will alsobe the fifth presidency of a member state that joined the European Unionin 2004. The subject matter of the six-month research, the results of whichare presented in the present work, was Lithuania’s preparation for its firstpresidency of the Council and the course of research was determined by thefollowing research questions: In what way will the changes introduced to theEuropean Union system of institutions by the Treaty of Lisbon as well asthe practice of former presidencies influence the Lithuanian presidency? Inwhat way will the preparation to presidency influence the Europeanization ofthe Lithuanian administration and the system of the European policy coordination?How does the Lithuanian government publicize the approachingpresidency? Are there any working meetings between Poland and Lithuaniain order to exchange information about good practices? What may be thepriorities of the Lithuanian presidency? What can affect them? Moreover,we asked the following questions regarding priorities: To what extent canLithuania use the presidency of the Council to promote and satisfy its owninterests at the European level? What will be the relationship between theEuropean Union and national interests? Which countries, especially Balticones, will Lithuania cooperate with in the priority areas? Having taken intoaccount the preparations to presidency so far, is it possible to predict if theLithuanian presidency will be reliable, efficient and effective?